Improved direct torque control of permanent magnet synchronous electrical vehicle motor with proportional-integral resistance estimator. - Hartani, Kada (Journal of electrical engineering & technology)
Electronic vehicles (EVs) require fast torque response and high drive efficiency. This paper describes a control scheme of fuzzy direct torque control of permanent magnet synchronous motor for EVs. This control strategy is extensively used in EV application. With direct torque control (DTC), the electromagnetic torque and stator flux can be estimated using the measured stator voltages and currents. The estimation depends on motor parameters except for the stator resistance. The variation of stator resistance due to changes in temperature or frequency downgrades the performance of DTC, which is controlled by introducing errors in the estimated flux linkages vector and the electromagnetic torque. Thus, compensation for the effect of stator resistance variation becomes necessary. This work proposes the estimation of the stator resistance and its compensation using a proportional-integral estimation method. An electronic differential has been also used, which has the advantage of replacing loose, heavy, and inefficient mechanical transmission and mechanical differential with a more efficient, light, and small electric motors that are directly coupled to the wheels through a single gear or an in wheel motor.